Deciphering the prolactin-thyroid-lipid nexus in type 2 diabetes and hypothyroidism: insights into metabolic interactions and dysregulation - Jamatia, Mandayal; Khan, Mohammad Nadeem; Kumar, Ashok (International Journal of Research in Medical Sciences, 2025)
Background: Prolactin, thyroid hormones, and lipid metabolism play critical roles in maintaining metabolic homeostasis. Their dysregulation in type 2 diabetes and hypothyroidism may contribute to disease progression and complications. This study investigates the associations between prolactin, thyroid function, lipid metabolism, and glycemic parameters in individuals with type 2 diabetes and hypothyroidism. Methods: A cross-sectional study was conducted on patients diagnosed with type 2 diabetes and hypothyroidism. Serum levels of fasting blood glucose (FBS), postprandial blood sugar (PPBS), glycated hemoglobin (HbA1c), thyroid hormones [free T3 (FT3), free T4 (FT4), and thyroid stimulating hormone (TSH)], lipid parameters, and prolactin were measured. Correlation analyses were performed to determine associations between prolactin, thyroid function, lipid profile, and glycemic markers. Results: Significant alterations were observed in metabolic parameters among diabetic and hypothyroid patients. Prolactin levels showed a significant negative correlation with HbA1c (r=-0.42, p<0.05) and triglycerides (TG) (r=-0.38, p<0.05), suggesting a potential role in metabolic regulation. A positive correlation was found between prolactin and thyroid hormones FT3 (r=0.44, p<0.05) and FT4 (r=0.39, p<0.05), highlighting the interplay between the pituitary-thyroid axis and metabolism. Conclusions: The findings emphasize the need for routine screening of thyroid function in diabetic patients and lipid profile monitoring in individuals with thyroid dysfunction to prevent metabolic complications. Prolactin may serve as a potential biomarker for metabolic dysregulation, warranting further investigation into its diagnostic and prognostic significance.